Influence of Halide Choice on Formation of Low‐Dimensional Perovskite Interlayer in Efficient Perovskite Solar Cells. Issue 2 (30th March 2022) - Liu, Xueping; Webb, Thomas; Dai, Linjie; Ji, Kangyu; Smith, Joel A.; Kilbride, Rachel C.; Yavari, Mozhgan; Bi, Jinxin; Ren, Aobo; Huang, Yuanyuan; Wang, Zhuo; Shen, Yonglong; et al.
Abstract : Recent advances in heterojunction and interfacial engineering of perovskite solar cells (PSCs) have enabled great progress in developing highly efficient and stable devices. Nevertheless, the effect of halide choice on the formation mechanism, crystallography, and photoelectric properties of the low‐dimensional phase still requires further detailed study. In this work, we present key insights into the significance of halide choice when designing passivation strategies comprising large organic spacer salts, clarifying the effect of anions on the formation of quasi‐2D/3D heterojunctions. To demonstrate the importance of halide influences, we employ novel neo‐pentylammonium halide salts with different halide anions (neoPAX, X=I, Br, or Cl). We find that regardless of halide selection, iodide‐based (neoPA)2 (FA)( n ‐1) Pb n I(3 n +1) phases are formed above the perovskite substrate, while the added halide anions diffuse and passivate the perovskite bulk. In addition, we also find the halide choice has an influence on the degree of dimensionality ( n ). Comparing the three halides, we find that chloride‐based salts exhibit superior crystallographic, enhanced carrier transport, and extraction compared to the iodide and bromide analogs. As a result, we report high power conversion efficiency in quasi‐2D/3D PSCs, which are optimal when using chloride salts, reaching up to 23.35%, and improving long‐term stability. Abstract : We systematically compare the difference of halide anions for the formation mechanism of quasi‐2D/3D heterojunctions based on novel organic ammonium halide salts. The results suggest that halide anions have significant differences in forming the n‐values in quasi‐2D phases and composition in 3D perovskite. The formed electron‐blocking quasi‐2D/3D heterojunction enables efficient carrier extraction and remarkable enhancement of PCE over 23%.